Changes in cognitive functioning after COVID‐19: A systematic review and meta‐analysis. Issue 5 (17th March 2022) - Crivelli, Lucia; Palmer, Katie; Calandri, Ismael; Guekht, Alla; Beghi, Ettore; Carroll, William; Frontera, Jennifer; García‐Azorín, David; Westenberg, Erica; Winkler, Andrea Sylvia; Mangialasche, Francesca; Allegri, Ricardo F.; et al.
Abstract: Introduction: We conducted a systematic review and meta‐analysis of the cognitive effects of coronavirus disease 2019 (COVID‐19) in adults with no prior history of cognitive impairment. Methods: Searches in Medline/Web of Science/Embase from January 1, 2020, to December 13, 2021, were performed following Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines.  A meta‐analysis of the Montreal Cognitive Assessment (MoCA) total score comparing recovered COVID‐19 and healthy controls was performed. Results: Oof 6202 articles, 27 studies with 2049 individuals were included (mean age = 56.05 years, evaluation time ranged from the acute phase to 7 months post‐infection). Impairment in executive functions, attention, and memory were found in post‐COVID‐19 patients.  The meta‐analysis was performed with a subgroup of 290 individuals and showed a difference in MoCA score between post‐COVID‐19 patients versus controls (mean difference = −0.94, 95% confidence interval [CI] −1.59, −0.29; P = .0049). Discussion: Patients recovered from COVID‐19 have lower general cognition compared to healthy controls up to 7 months post‐infection.